1995
DOI: 10.1210/endo.136.5.7720683
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide mediates tumor necrosis factor effects on P450-aromatase activity in cultured granulosa cells.

Abstract: In [3H]serine-labelled granulosa cells treatment with TNF alpha (10 ng/ml) resulted in a transient decrease in cellular [3H]sphingomyelin and generation of [3H]ceramide that remained elevated 60 min later. In cells labelled with [methyl-14C]choline, TNF alpha induced a similar reduction in [14C]sphingomyelin content that was accompanied by a sustained elevation in [14C]phosphorylcholine levels. In FSH-primed cells, TNF alpha inhibited P450-AROM activity in a dose-dependent manner, an effect that was also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…These observations support the hypothesis of an involvement of PLD in the stimulation of aldosterone secretion by S1P. Nonetheless, although ceramide blocks PLD, this may not be the only reason for the inhibition of aldosterone secretion by this sphingolipid, as ceramides can also affect the activities or the expression of enzymes that participate in steroid synthesis (52,65).…”
Section: S1p-stimulated Aldosterone Secretion Is Mediated By Pldsupporting
confidence: 82%
“…These observations support the hypothesis of an involvement of PLD in the stimulation of aldosterone secretion by S1P. Nonetheless, although ceramide blocks PLD, this may not be the only reason for the inhibition of aldosterone secretion by this sphingolipid, as ceramides can also affect the activities or the expression of enzymes that participate in steroid synthesis (52,65).…”
Section: S1p-stimulated Aldosterone Secretion Is Mediated By Pldsupporting
confidence: 82%
“…In this context, studies have shown that radiation may activate PKCa via diacylglycerol (DAG) generation (Chmura et al, 1996(Chmura et al, , 1997aBruno et al, 1998). As mentioned above, activation of PKC by phorbol esters blocked in most cell types tested radiation-induced ceramide generation and apoptosis (Haimovitz-Friedman et al, 1994a, b;Santana et al, 1995;Chmura et al, 1996;Allan-Yorke et al, 1998;Bruno et al, 1998). Conversely, pharmacologic inhibition of PKC enhanced radiation-induced cell death (Hallahan et al, 1992b).…”
Section: X-irradiationmentioning
confidence: 97%
“…Conversely, pharmacologic inhibition of PKC enhanced radiation-induced cell death (Hallahan et al, 1992b). The mechanism by which TPA and DAG inhibit apoptosis apparently via inhibition of SMase activation (Santana et al, 1995); in some cells, this may occur through upregulation of BCL-2 or BCL-XL (Hallahan et al, 1992a;Uckun et al, 1993). bFGF similarly protected endothelial cells against radiationinduced apoptosis, in part via activation of the PKC and MAPK pathways (Haimovitz-Friedman et al, 1994a;Verheij et al, 1996), but also via inhibition of SMasemediated generation of ceramide (Haimovitz-Friedman, unpublished).…”
Section: X-irradiationmentioning
confidence: 99%
“…Sphingomyelin and its hydrolysis product, ceramide levels were monitored by the method of Santana et al (1995) with slight modifications. A20 cells were labeled with 2 µCi/ml of [ 3 H]serine in the minimum essential medium for 18 h and treated with anti-Fas monoclonal antibody for various time periods.…”
Section: Sphingomyelin Hydrolysis Assaymentioning
confidence: 99%